Functional and Radiological Outcome of Anterior Cervical Discectomy and Titanium Cage Fusion in the Management of Patients with Degenerative Cervical Spine Disease - Sardar Sohail Afsar, Yaqoob Ur Rehman, Akbar Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The causes of cervical radiculopathy include trauma, disc herniation, instability, spondylosis and, in rare cases, malignancies. Degenerative spinal disorders are often treated by anterior cervical discectomy. Objective: To assess the functional and radiological outcome of anterior cervical discectomy and titanium cage fusion in the management of patients with degenerative cervical spine disease Methodology: The current study was descriptive study carried out at the orthopedic department, Qazi Hussain Ahmad Medical College, Nowshera from August 2021 to August 2022. All the relevant laboratory and radiological investigations were carried out for the enrolled patients. Cervical radiographs were examined for fusion, cage subsidence, and kyphosis at each visit. The functional outcomes, quality of life and pain level was determined for all the patients. IBM SPSS version 23 was employed for analysis of data. Results: In the current study, totally 50 patients were enrolled. The male participants in this study were 30 (60%) while female patients were 20 (40%). The mean age of the patients was 53 (±5.32). The pre-operative mean NDI, VAS and EQ-5D-5L index was 42 (5.90), 8.11 (2.11) and 0.54 (0.01) respectively while the post-operative mean NDI, VAS and EQ-5D-5L index was 19 (2.81), 2 (1.88) and 0.75(0.01) respectively (p=˂0.05). In all the enrolled patients radiographical fusion was achieve successfully. Segmental subsidence was reported in 2 (4%) patients while kyphosis was not observed in any of our patients. Conclusion: Our study concludes that in patients with symptomatic degenerative cervical spine disease, the anterior cervical discectomy and titanium cage fusion is an effective and safe surgical procedure with excellent functional and radiological outcome. Our study observed minimal complication rate by using this procedure. Keywords: Radiological outcome; Anterior cervical discectomy; titanium cage fusion; degenerative cervical spine disease